PEMBERDAYAAN KELUARGA DALAM DAN PENCEGAHAN DEMAM BERDARAH DI KELURAHAN SRI MERANTI - Arneliwati Arneliwati; Aminatul Fitri; Herlina Herlina; Ari Rahmat Aziz; Didi Kurniawan; Reni Zulfitri; Musfardi Rustam; Nopriadi Nopriadi (INSTITUT KESEHATAN DELI HUSADA, 2022)
This study aims to see an increase in family knowledge, attitudes, and actions in the prevention of Dengue Hemorrhagic Fever (DHF) after socialization of family empowerment on the prevention of Dengue Hemorrhagic Fever in RW 12, Sri Meranti Village and training and education on mosquito eradication by examining larvae and spreading abate powder. The research design used a quasi-experimental pre- and post-test design on 50 respondents in the RW 12 area of Sri Meranti Village. This study used a questionnaire instrument. Test analysis using dependent T test analysis. The results showed a significant difference between family knowledge before and after being given counseling related to Dengue Hemorrhagic Fever with a p Value of 0.00. It is hoped that families will apply the knowledge they have gained in socialization, with the hope that dengue cases will decrease or even disappear. Keywords: Dengue Fever, Family Empowerment, , Family Knowledge